The effects of the ventral truncal vagotomy on the functions of the forestomach and abcmasum in sheep - Kürşat TURGUT; Abdullah BAŞOĞLU; Yilmaz KOÇ; Kemal ÇİFTÇİ; Saadettin TIPIRDAMAZ; Veysi ASLAN; Mehmet GÜRBİLEK; Mahmut OK; Cevat ÖZKAN (Eurasian Journal of Veterinary Sciences)
In this study, a total of 12 sheep was used. 6 of which were usedas a control group on which only paramedian laparatomy was performed. 6 of which were used as an experimental group on wihch ventral truncal vagotomy was performed via paramedian laparatoy. All the clinical, heamotological, biochemical and electrocardiographic examinations were performed for a month during the experiment. During the study elinical symptoms of vagus indigestion which has been deseribed by Hoflund were not observed. There was significant decreaments in the respiration rate of experimental group at the 4th, 1oth and 2oth day of the experiment. Plasma BE values were significantly increased at the 1 ot h, 2oth and 3oth day of axperiment in the experimental group. Rumen cı- ffilncentration was significantly increased only at the 15t day of the experiment in the experimental group. Plasma gastrin concentration was decr$ased only at the sceond day of the experiment in the experimental group. Sinus arret was recorded during the electrocardiographic examination ~f the two groups of sheep at the diferent time. Theresult of the study showed that functional disorders of the nervus vagus did not play a role of the pathogenesis of vagus indigestion.